2020
DOI: 10.1155/2020/6834236
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Kallikrein 1 Improves Erectile Dysfunction of Streptozotocin-Induced Diabetic Rats by Inhibition of Excessive Oxidative Stress and Activation of the PI3K/AKT/eNOS Pathway

Abstract: Objective. To investigate the protective effects and mechanisms of human tissue kallikrein 1 (hKLK1) on type 1 diabetes mellitus- (DM-) induced erectile dysfunction in rats. Materials and Methods. The homozygous transgenic rats (TGR) harboring the hKLK1 gene and age-matched wild-type Sprague Dawley rats (WTR) were involved, and intraperitoneal injection of streptozotocin was utilized to induce diabetes in rats. Forty-eight-week-old male rats were randomly divided into a WTR group, TGR group, diabetic WTR group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In addition to the regulation of blood vessels, nerves, the endocrine system, and other factors, abnormalities in penile erection can also be closely related to the vasomotor function of the vascular smooth muscle. Previous studies have found that during the occurrence of ED, there is an increase in the number of collagen fibers in the penile cavernous body; fibrotic changes can also occur, along with limitations in smooth muscle relaxation and contraction [ 10 ]. The PI3K/Akt/mTOR pathway is widely distributed in the penile vascular smooth muscle and facilitates the regulation of diastolic function in the smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the regulation of blood vessels, nerves, the endocrine system, and other factors, abnormalities in penile erection can also be closely related to the vasomotor function of the vascular smooth muscle. Previous studies have found that during the occurrence of ED, there is an increase in the number of collagen fibers in the penile cavernous body; fibrotic changes can also occur, along with limitations in smooth muscle relaxation and contraction [ 10 ]. The PI3K/Akt/mTOR pathway is widely distributed in the penile vascular smooth muscle and facilitates the regulation of diastolic function in the smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have confirmed that PI3K and AKT undergo significant activation in brainstem tissue from rat models of migraine [ 9 ]. Furthermore, the levels of essential neurotransmitters in the brain, such as serotonin, were significantly reduced, thus proving that the PI3K/Akt/mTOR signaling pathway is one of the dominant mechanisms underlying migraine [ 10 ]. The occurrence of ED is due to a combination of factors, including blood vessels, nerves, and endocrine factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that any treatment that can reduce oxidative stress may attenuate myocardial I/R injury ( 34 – 36 ). It has been previously reported that hTK1 can improve erectile dysfunction of streptozotocin-induced diabetic model rats and attenuate salt-induced renal fibrosis via inhibition of oxidative stress ( 8 , 37 ). Furthermore, a previous study demonstrated that free TIMP1 and magnetic nanoparticle-bound TIMP1 significantly reduced ROS production in HIV-infected neuroblastoma cells ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue kallikrein 1 (TK1), a glycoprotein that belongs to the serine proteinase superfamily, can cleave low-molecular-weight kininogen into a number of bioactive kinin peptides, including kininogens and kallikreins ( 7 ). Vasoactive kinins serve a beneficial role in a number of cardiovascular, cerebrovascular and renal diseases ( 8 ). A previous study revealed that hTK1 gene-modified mesenchymal stem cells display protective effects against cardiac injury following MI via suppressing apoptosis and inflammation, and promoting neovascularization ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the published method, 24 corpus cavernosum smooth muscle cells (CCSMCs) were extracted and purified via the differential wall adhesion method from the CC of 8-week-old healthy male SD rats. CCSMCs were cultured in Dulbecco's modified Eagle's medium (DMEM, low-glucose, HyClone, USA) containing 10% fetal bovine serum (FBS; Gibco, USA), 1% 100 ng/ml streptomycin, and 1% 100 U/ml penicillin under standardized conditions (5% CO2, 37 • C).…”
Section: Culture and Identification Of Cells And Drug Treatmentsmentioning
confidence: 99%